2022
DOI: 10.3389/fimmu.2022.862049
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Key Pyroptosis-Related Genes and Distinct Pyroptosis-Related Clusters in Periodontitis

Abstract: AimThis study aims to identify pyroptosis-related genes (PRGs), their functional immune characteristics, and distinct pyroptosis-related clusters in periodontitis.MethodsDifferentially expressed (DE)-PRGs were determined by merging the expression profiles of GSE10334, GSE16134, and PRGs obtained from previous literatures and Molecular Signatures Database (MSigDB). Least absolute shrinkage and selection operator (LASSO) regression was applied to screen the prognostic PRGs and develop a prognostic model. Consens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 89 publications
0
10
0
Order By: Relevance
“…The NLRP3/caspase-1/GSDMD pathway leads to pyroptosis and is significantly related to inflammation. Pyroptosis has been recently suggested as one of the pathways implicated in the pathogenesis of periodontitis [ 8 , 9 ]. In addition, hyperglycemia, the hallmark of diabetes mellitus, impairs the function of macrophage and induces pyroptosis, which contributes to cell senescence and low-degree inflammatory state in periodontal tissue [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The NLRP3/caspase-1/GSDMD pathway leads to pyroptosis and is significantly related to inflammation. Pyroptosis has been recently suggested as one of the pathways implicated in the pathogenesis of periodontitis [ 8 , 9 ]. In addition, hyperglycemia, the hallmark of diabetes mellitus, impairs the function of macrophage and induces pyroptosis, which contributes to cell senescence and low-degree inflammatory state in periodontal tissue [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…We also found correlations between the 17 pyroptosis-related hub genes and 13 immune cell types. The relationship between pyroptosis regulators and immune infiltrate characterization has been discussed in diseases, including cancer and periodontitis (99,100). In this study, we identified 11 cell types from the scRNA-seq dataset.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we used the "normalize between arrays" function of the "limma" package to reduce the effect of batch effects [ 19 ]. We downloaded a total of 2052 genes related to oxidative stress from MsigDB ( http://www.gsea-msigdb.org/gsea/downloads.jsp ) [ 20 ], GeneCards ( https://www.genecards.org/ ) [ 21 ], and NCBI ( https://www.ncbi.nlm.nih.gov/ ) databases [ 22 ]. 1387 genes related to mitochondrial stress were identified from the MsigDB database and Human MitoCarta 3.0 ( https://www.broadinstitute.org/mitocarta/ ) database [ 23 ].…”
Section: Methodsmentioning
confidence: 99%